Pemberdayaan Masyarakat Melalui Kegiatan Bimbingan Sore kepada Siswa SDM Karuni, Sumba Barat Daya, NTT - Welhem Mine Wadu; Timotius Woda Napu; Antonius Lende (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Abstract Numeracy skills at the elementary education level are essential competencies that go beyond basic arithmetic, encompassing the ability to understand, use, and interpret quantitative concepts in everyday life. However, various studies indicate that Indonesian elementary school students still demonstrate low numeracy performance, particularly in solving basic arithmetic operations and contextual problems. A similar condition was found at SDM Karuni in Letekonda Selatan Village, Southwest Sumba Regency, where students experienced difficulties in basic mathematics operations and lacked learning support outside school hours. This community service study aimed to improve students’ numeracy skills through an afternoon tutoring program based on contextual learning approaches, educational games, and the debit-credit method. The program was conducted over three months involving 18 students selected through purposive sampling. Data were collected using pre-tests, formative tests, and post-tests, and analyzed descriptively along with N-Gain calculations. The results showed a significant improvement in students’ numeracy skills, with the average score increasing from 46.11 in the pre-test to 90.28 in the post-test. The N-Gain value of 0.82 was categorized as high, indicating that the afternoon tutoring program was effective in improving students’ understanding of basic arithmetic operations. Therefore, this program can serve as an effective alternative instructional strategy to enhance numeracy skills in elementary school students, particularly in areas with limited access to learning assistance. Keywords: numeracy; tutoring; rural education; mathematics; basic operations Abstrak Kemampuan numerasi pada jenjang sekolah dasar merupakan keterampilan penting dalam membangun kemampuan berpikir logis, pemecahan masalah, serta pemahaman konsep kuantitatif dalam kehidupan sehari-hari. Namun, masih banyak siswa sekolah dasar di Indonesia yang mengalami kesulitan dalam menguasai operasi hitung dasar dan menyelesaikan soal kontekstual. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kemampuan numerasi siswa SDM Karuni, Kabupaten Sumba Barat Daya, melalui kegiatan bimbingan sore. Program dilaksanakan selama tiga bulan dengan melibatkan 18 siswa yang dipilih menggunakan teknik purposive sampling. Metode yang digunakan adalah pembelajaran kontekstual yang dipadukan dengan permainan edukatif serta pendekatan debet dan kredit, dengan fokus pada empat operasi dasar matematika yaitu penjumlahan, pengurangan, perkalian, dan pembagian. Data dikumpulkan melalui pre-test, tes formatif, dan post-test, kemudian dianalisis secara deskriptif menggunakan rata-rata nilai dan perhitungan N-Gain. Hasil penelitian menunjukkan peningkatan kemampuan numerasi siswa yang signifikan, dengan rata-rata nilai meningkat dari 46,11 pada pre-test menjadi 90,28 pada post-test. Nilai N-Gain sebesar 0,82 termasuk kategori tinggi. Dengan demikian, program bimbingan sore berbasis kontekstual terbukti efektif dalam meningkatkan kemampuan numerasi siswa dan dapat menjadi alternatif strategi pendampingan belajar di daerah dengan keterbatasan akses pendidikan. Kata Kunci: numerasi; bimbingan_belajar; pendidikan_anak_terpencil; matematika; operasi_dasar